Connexin 43 in Mitochondria: What Do We Really Know About Its Function? - Boengler, Kerstin; Leybaert, Luc; Ruiz-Meana, Marisol; Schulz, Rainer (Frontiers in Physiology, 2022)
Connexins are known for their ability to mediate cell-cell communication via gap junctions and also form hemichannels that pass ions and molecules over the plasma membrane when open. Connexins have also been detected within mitochondria, with mitochondrial connexin 43 (Cx43) being the best studied to date. In this review, we discuss evidence for Cx43 presence in mitochondria of cell lines, primary cells and organs and summarize data on its localization, import and phosphorylation status. We further highlight the influence of Cx43 on mitochondrial function in terms of respiration, opening of the mitochondrial permeability transition pore and formation of reactive oxygen species, and also address the presence of a truncated form of Cx43 termed Gja1-20k. Finally, the role of mitochondrial Cx43 in pathological conditions, particularly in the heart, is discussed.